External root resorption: Different etiologies explained from the composition of the human root-close periodontal membrane - Inger Kjaer (Wolters Kluwer Medknow Publications, 2013)
Introduction: This paper summarizes different conditions, which have a well-known influence on the resorption of tooth roots. It also highlights factors important for individual susceptibility to root resorption. Furthermore, the paper focuses on idiopathic root resorption where the provoking factor is not known. The Hypothesis: The several different disturbances causing root resorption can be either orthodontically provoked or acquired by trauma, virus or congenital diseases. It is presumed that all these conditions lead to inflammatory processes in the three main tissue layers, comprising the peri-root sheet. Evaluation of the Hypothesis: This paper explains how different etiologies behind root resorption and how different phenotypic traits in root resorption can be understood from immunohistochemical studies of the human periodontal membrane close to the root and thus, gain a new understanding of the phenomenon of root resorption.